Impact of tunnel enlargement on patient-reported outcomes following isolated posterior cruciate ligament reconstruction - Kun-Han Lee; Tai-Jung Huang; Hsuan-Hsiao Ma; Kun-Hui Chen; Hsiao-Li Ma; En-Rung Chiang (Journal of Orthopaedic Surgery and Research)
Abstract Background Tunnel enlargement (TE) might jeopardize knee function and ligament stability after revision surgery of anterior cruciate ligament reconstruction. To date, only few studies concern TE following posterior cruciate ligament reconstruction (PCLR). This study aims to determine TE after isolated PCLR and its relationship with patient-reported outcomes. Methods Patients who received primary isolated PCLR were screened. Femoral and tibial tunnel size was measured using an anteroposterior and lateral view of radiographs at least 6 months after surgery. TE is considered significant if the width of the bone tunnel increases by 25% over the drilled size. Patient-reported outcomes were determined using the subjective International Knee Documentation Committee (IKDC) score and the Lysholm score. The association between patient baseline characteristics, patient-reported scores, and the severity of TE was investigated. Results Fifty-four patients were enrolled. TE was observed in 15 femoral tunnels and in 14 tibial tunnels. The average TE rate is 17.9% for femur and 7.9% for tibia. No correlation between the level of TE and patient-reported outcomes is noted. However, when patients are classified into TE and non-TE group on the basis of 25% of enlargement, those who exhibit femoral TE have a lower postoperative Lysholm score (81.1 ± 13.0 vs. 90.5 ± 12.3, P = 0.031) and those with tibial TE have a lower postoperative IKDC score (76.0 ± 17.4 vs. 87.1 ± 12.1, P = 0.031). Conclusions The overall incidence of femoral and tibial TE after isolated PCLR is low. However, femoral and tibial TE are correlated with worse patient-reported outcomes in terms of the lower postoperative Lysholm and IKDC scores.